2016
DOI: 10.1126/science.aaf4610
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal association as a primary control of the CO 2 fertilization effect

Abstract: Plants buffer increasing atmospheric CO 2 concentrations through enhanced growth, but the question whether nitrogen availability constrains the magnitude of this ecosystem service remains unresolved. Synthesizing experiments from around the world, we show that CO 2 fertilization is best explained by a simple interaction between nitrogen availability and mycorrhizal association. Plant species that associate with ectomycorrhizal fungi show a strong biomass increase (30 ± 3%, P<0.001) in response to elevated CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
378
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 511 publications
(393 citation statements)
references
References 138 publications
11
378
1
3
Order By: Relevance
“…This idea gained recent support by Terrer et al (2016) who found that plant species colonized by ECM fungi were able to sustain increased growth under elevated concentrations of carbon dioxide despite low soil N availability a phenomenon that has also been reported by others (Drake et al 2011). One possible mechanism for this sustained growth response is that ECM fungi, supplied with additional C from host plants, are able to mine recalcitrant compounds for N thereby increasing plant N uptake (Phillips et al 2012;Terrer et al 2016). To gain a more complete picture of the organisms and conditions driving the decomposition of the most distal root orders, there are a number of questions that require answers (Table 1).…”
Section: Final Thoughtsmentioning
confidence: 89%
“…This idea gained recent support by Terrer et al (2016) who found that plant species colonized by ECM fungi were able to sustain increased growth under elevated concentrations of carbon dioxide despite low soil N availability a phenomenon that has also been reported by others (Drake et al 2011). One possible mechanism for this sustained growth response is that ECM fungi, supplied with additional C from host plants, are able to mine recalcitrant compounds for N thereby increasing plant N uptake (Phillips et al 2012;Terrer et al 2016). To gain a more complete picture of the organisms and conditions driving the decomposition of the most distal root orders, there are a number of questions that require answers (Table 1).…”
Section: Final Thoughtsmentioning
confidence: 89%
“…However, a stimulation of enzyme synthesis by N was not observed in this study (Table 2), and (4) finally, microbial N mining might depend on the association of plants with mycorrhizal fungi, an effect that we would have underestimated in our laboratory experiment. Ectomycorrhiza-the dominant mycorrhiza in boreal forests-have been linked to the release of available N from SOM polymers (Lindahl et al 2007;Talbot et al 2013), and to increased N mining under elevated CO 2 (Drake et al 2011;Terrer et al 2016). Microbial N mining might thus depend not on plantsoil C allocation in general, but specifically on the allocation of C to certain mycorrhiza.…”
Section: Discussionmentioning
confidence: 99%
“…Janssens et al, 2010;Vicca et al, 2012;Fernández-Martínez et al, 2014). Moreover, nutrient availability can modify ecosystem responses to global atmospheric and climatic changes, such as nitrogen (N) deposition (From et al, 2016), increasing CO2 levels (Norby et al, 2010;Terrer et al, 2016), warming (Dieleman et al, 2012) and drought (Friedrich et al, Biogeosciences Discuss., https://doi.org/10.5194/bg-2017-372 Manuscript under review for journal Biogeosciences Discussion started: 2 November 2017 c Author(s) 2017. CC BY 4.0 License.…”
Section: Introductionmentioning
confidence: 99%